A molecular dynamics simulation study of PVT properties for H2O/H2/CO2 mixtures in near-critical and supercritical regions of water. (14th June 2018) - Yang, Xueming; Xu, Jiangxin; Wu, Sihan; Yu, Meng; Hu, Bo; Cao, Bingyang; Li, Jiahu
Abstract: Supercritical water gasification technology is an efficient and clean way to use the coal. This technology can convert carbon and hydrogen elements of coal into the mixtures of H2 O/H2 /CO2 that can be used for electricity generation. The acquisition of PVT properties of H2 O/H2 /CO2 mixtures is one of the most critical issues in realizing the design and operation of thermal power generation system using this technology. However, no experimental, theoretical and simulation studies exist regarding the PVT properties of H2 O/H2 /CO2 in the near-critical and supercritical regions of water. In this paper, the molecular dynamics simulations of the PVT properties of H2 O/CO2 mixtures are carried out and the theoretical calculations are conducted based on the equation of state, and the results are compared with the experimental values. Moreover, the PVT properties for H2 O/H2 mixtures and H2 O/H2 /CO2 mixtures in the near-critical and supercritical regions of water are predicted using molecular dynamics simulation and compared with the calculation results of the equation of state. The results of this paper are of great significance to the development of supercritical water gasification of coal, and could offer the reference for the application of H2 O/H2 /CO2 mixtures in practical production. Highlights: The PVT properties for H2 O/H2 /CO2 mixtures in near-critical and supercritical regions of water are predicted. The PVT properties for H2 O/H2 mixtures in near-critical and supercritical regions of water are investigated. The predictions by MD simulations are compared with those by the PR equation of state. The RDFs of the H2 O/H2 /CO2 ternary mixtures for the MD simulations are discussed.